0007 Daytime Sleep in Night Shift Workers: Quantifying the Role of Circadian Misalignment. (27th May 2020) - Mann, E; Sagong, C; Cuamatzi Castelan, A; Singh, M; Roth, T; Drake, C L; Cheng, P
Abstract: Introduction: Circadian misalignment is commonly cited as a culprit of daytime sleep disturbances in night shift workers; however, the specific impact and magnitude that circadian misalignment has on daytime sleep has not been well-characterized in larger samples of night shift workers. Methods: Participants included fixed-night shift workers (n=52, ages 18–50) who completed an 8-hour daytime polysomnography (PSG) in the lab following a night shift. Measures of sleep disturbances included: difficulty falling asleep (sleep onset latency [SOL], latency to persistent sleep [LPS]), difficulty staying asleep (sleep efficiency [SE], wake after sleep onset [WASO]), and sleep duration (total sleep time [TST]). Melatonin samples were collected hourly for 24 hours under dim light (<10 lux) and used to determine dim light melatonin offset (DLMOff). Circadian misalignment (CM) was calculated as the time difference between bedtime and DLMOff (higher values represented sleeping after DLMOff), and correlated with PSG sleep variables. Results: CM was significantly associated with difficulty staying asleep (WASO: r=0.48, p<0.001; SE: r=-0.45, p<0.001), and sleep duration (TST: r=-0.38, p<0.01). Specifically, every 3 hours of CM on average added 19.2 minutes of WASO and reduced TST by 15 minutes. In contrast, CM was not significantly correlated with sleep onset difficulties (SOL: r=-0.27; LPS: r=-0.02). Conclusion: These data suggest that circadian misalignment in shift workers may be a better predictor of difficulties staying asleep and sleep duration during the day relative to difficulties falling asleep. Because longer work hours (10–12 hours) are common in night shift worker, it may be that sleep initiation difficulties associated with circadian misalignment is masked by elevated fatigue or an increased homeostatic drive from prolonged wakefulness. These results may help guide decisions about the magnitude of phase shifts required (e.g., with light therapy) for the desired improvement in daytime sleep. Support: Support for this study was provided to PC by the NHLBI (K23HL138166)